PENGARUH MANAJEMEN LABA, PROFITABILITAS, DAN LIKUIDITAS TERHADAP KEBIJAKAN DIVIDEN - Mentari Chandra Tjiang; Fransiskus Randa; Marselinus Asri (Fakultas Ekonomi dan Bisnis Universitas Atma Jaya Makassar, 2018)
This study aims to investigate the effect of earnings management, profitability andliquidity on dividend policy. The independent variables used are earningsmanagement, profitability, and liquidity. The dependent variable used is dividendpolicy. The population used in this study is a manufacturing company listed on theIndonesia Stock Exchange with the period of 2014-2016. Sample Method used inthis research is purposive sampling method with certain criteria and use secondarydata in the form of annual report and company financial report. The hypothesis in thisstudy was tested using multiple linear regression.The results of this study indicatethat the variable of earnings management has a positive and insignificant effect ondividend policy. While profitability research results have a positive and significanteffect on dividend policy. And the results of the research of liquidity have a negativeand insignificant influence on dividend policy. This research is expected to giveconsideration to the company to improve its performance well in assessing company.So as to increase the confidence of investors in making decisions